2021
DOI: 10.1093/biosci/biab086
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Ecological Transformation: Mental Models, External Constraints, and Manager Decision-Making

Abstract: Ecological transformation creates many challenges for public natural resource management and requires managers to grapple with new relationships to change and new ways to manage it. In the context of unfamiliar trajectories of ecological change, a manager can resist, accept, or direct change, choices that make up the resist-accept-direct (RAD) framework. In this article, we provide a conceptual framework for how to think about this new decision space that managers must navigate. We identify internal factors (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 110 publications
0
28
0
1
Order By: Relevance
“…Unlike previous applications of the RAD framework that focus on ecological transformations, where managers are the ones undertaking RAD strategies, our application of the framework to fishery SESs includes managers, fishers, and supply chain actors as participants with agency to resist , accept , or direct social ecosystem transformation. Managers can facilitate or constrain the number and type of options in any of the RAD strategies available to system participants via regulatory, policy, and management decisions (Clifford et al, 2022 ), yet how system participants act within that decision space determines the transformation's broader social outcomes. This expansion of the RAD framework better reflects the true nature of SESs, where humans are participants within the system, not just external managers of the system's ecological components.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous applications of the RAD framework that focus on ecological transformations, where managers are the ones undertaking RAD strategies, our application of the framework to fishery SESs includes managers, fishers, and supply chain actors as participants with agency to resist , accept , or direct social ecosystem transformation. Managers can facilitate or constrain the number and type of options in any of the RAD strategies available to system participants via regulatory, policy, and management decisions (Clifford et al, 2022 ), yet how system participants act within that decision space determines the transformation's broader social outcomes. This expansion of the RAD framework better reflects the true nature of SESs, where humans are participants within the system, not just external managers of the system's ecological components.…”
Section: Discussionmentioning
confidence: 99%
“…The actions of fisheries stakeholders are motivated by political and regulatory systems, economic factors, norms, and value systems. Thus, the structure and scale of social systems drive receptivity to management interventions and can affect the feasibility of RAD options for both social and ecological processes (Clifford et al, 2022). Fishery stocks are common pool resources and coordination among stakeholder groups is a prerequisite for effective management (Ostrom, 1990).…”
Section: Improving Controll Ab Ilit Ymentioning
confidence: 99%
“…In addition to individual and cultural influences on mental models that can drive decisions for managing biological invasions, a third and important contributor to mental models is the understanding of the environmental system (Clifford et al, 2022). Social science research has shown that individuals can vary widely in their knowledge of introduced species, impacts, and consequent preferences for managing them (Niemiec et al, 2017; Shackleton et al, 2019).…”
Section: Social Foundations Of Managing Biological Invasionsmentioning
confidence: 99%
“…management decision space stakeholders operate within (Clifford et al, 2022). More specifically, preferences for RAD alternatives (i.…”
Section: Pathwaymentioning
confidence: 99%